Chordoid Glioma of the Third Ventricle, a Rare Tumor with an Unexpected Outcome - Cunha, Pedro Ribeiro da; Rebelo, Olinda; Barbosa, Marcos (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Chordoid glioma is a rare tumor of the third ventricle whose imaging features are difficult to distinguish from other more common lesions in this location. There are only 83 cases described so far in the literature. Although gross total resection (GTR) is the treatment of choice, immediate postoperative mortality with this approach can be as high as 29%, and morbidity among survivors can reach 67%. We report a case of a male patient of advanced age, with a third ventricle mass lesion, who presented with a progressive right temporal hemianopia. Imaging was compatible with craniopharyngioma, meningioma or even metastasis. Chordoid glioma was not considered in the differential diagnosis. The patient underwent surgery and GTR was achieved. There were no postoperative complications, and the patient was discharged from the hospital three weeks later. Unexpectedly, two days afterwards, he suffered a major brainstem hemorrhagic stroke and, unfortunately, died.
Keywords: chordoid glioma; third ventricle; gross total resection